Adjuvant everolimus in high-risk diffuse large B-cell lymphoma: final results from the PILLAR-2 randomized phase III trial - Witzig, T E; Tobinai, K; Rigacci, L; Ikeda, T; Vanazzi, A; Hino, M; Shi, Y; Mayer, J; Costa, L J; Bermudez Silva, C D; Zhu, J; Belada, D; et al. (Annals of oncology, 2018)
BACKGROUND: Patients with diffuse large B-cell lymphoma (DLBCL) with an International Prognostic Index (IPI) ≥3 are at higher risk for relapse after a complete response (CR) to first-line rituximab-based chemotherapy (R-chemo). Everolimus has single-agent activity in lymphoma. PILLAR-2 aimed to improve disease-free survival (DFS) with 1 year of adjuvant everolimus. PATIENTS AND METHODS: Patients with high-risk (IPI ≥3) DLBCL and a positron emission tomography/computed tomography-confirmed CR to first-line R-chemo were randomized to 1 year of everolimus 10 mg/day or placebo. The primary end point was DFS; secondary end points were overall survival, lymphoma-specific survival, and safety. RESULTS: Between August 2009 and December 2013, 742 patients were randomized to everolimus (n = 372) or placebo (n = 370). Median follow-up was 50.4 months (range 24.0-76.9). Overall, 47% of patients were ≥65 years, 50% were male, and 42% had an IPI of 4 or 5. 48% and 67% completed everolimus and placebo, respectively. Primary reasons for everolimus discontinuation versus placebo were adverse events (AEs; 30% versus 12%) and relapsed disease (6% versus 13%). Everolimus did not significantly improve DFS compared with placebo (hazard ratio 0.92; 95% CI 0.69-1.22; P = 0.276). Two-year DFS rate was 77.8% (95% CI 72.7-82.1) with everolimus and 77.0% (95% CI 72.1-81.1) with placebo. Common grade 3/4 AEs with everolimus were neutropenia, stomatitis, and decreased CD4 lymphocytes. CONCLUSIONS: Adjuvant everolimus did not improve DFS in patients already in PET/CT-confirmed CR. Future approaches should incorporate targeted agents such as everolimus with R-CHOP rather than as adjuvant therapy after CR has been obtained. CLINICALTRIALS.GOV: NCT00790036.
Keywords: dospělí; Doxorubicin; Kaplan-Meier Estimate; Antibodies, Monoclonal, Murine-Derived; prednison; Cyclophosphamide; Female; Everolimus; Adult; ženské pohlaví; Kaplanův-Meierův odhad; myší monoklonální protilátky; mladý dospělý; Neoplasm Recurrence, Local; přežití bez známek nemoci; adjuvantní chemoterapie; lidé; Antineoplastic Agents; protinádorové látky; difúzní velkobuněčný B-lymfom; Rituximab; Prednisone; everolimus; Aged, 80 and over; Antineoplastic Combined Chemotherapy Protocols; Lymphoma, Large B-Cell, Diffuse; protokoly protinádorové kombinované chemoterapie; protinádorové látky imunologicky aktivní; Humans; Middle Aged; etoposid; Male; Aged; rituximab; Young Adult; doxorubicin; lokální recidiva nádoru; Chemotherapy, Adjuvant; Disease-Free Survival; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Etoposide; cyklofosfamid; Vincristine; Antineoplastic Agents, Immunological; vinkristin